Analysis of the Precast Half Slab Method in Batang I Industrial Workers Flats Development Project - Iqbal Muttaqin; Nasyiin Faqih; Agus Juara (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2023)
This study aims to analyze the application of Precast Half Slab formwork with conventional formwork in terms of cost, time, and implementation stages. The method used in this study is the precast half slab method. The Batang I Industrial Worker Flats project is in the Batang Integrated Industrial Estate. In the highly advanced construction era, many projects compete to innovate to produce a fast and efficient building. This Project uses the precast half slab method, where half of the floor slab is printed offsite (precast) with a thickness of 7 cm, and the other half is in place (topping 5.5 cm). This final Project analyzes the precast half slab method used by comparing it to the conventional method in terms of cost and time, so it can be seen which method is more profitable. The precast half-slab method analysis focuses on calculating the direct cost of conventional half-slab precast in terms of materials, tools, and worker wages, as well as calculating the time needed for each job.